Algorithm of educational motivation formation of professional education applicants - Bakatanova, V.; Potyomkina, K. (Problems of Engineer-Pedagogical Education, 2021)
In article features of applicants training of professional education – students of the highest and pupils of professional educational institutions are revealed. The carried-out analysis of references allowed to reveal certain contradictions between incorrectly picked up means and methods of training of common students and pupils` cultural and general education levels formation, on the one hand, both requirements of an education system and needs of trainees, with another. For the purpose of determination of the current level and the direction of motivation there was a carriedout questioning of UIPA students and pupils of professional (professional) educational institutions and also questioning on identification of the reasons of a certain motivation. Using results of the conducted survey of students and pupils of professional education institutions and also the idea of pedagogical system developed by N.V. Kuzmina psychology and pedagogical conditions of students educational motivation formation were defined. According to certain psychology and pedagogical conditions of students educational motivation formation its algorithm was developed. It is constructed so that to have an opportunity to influence the reasons of a certain motivation within the program of training of specialists and personal experience of the teacher. To advantages of an algorithm it is possible to carry the sufficient accuracy of determination of the current level of motivation to training and also identification of positive and negative factors of educational process which influence motivation level. Also the algorithm considers the current level of the available knowledge, skills of students (pupils). Among shortcomings, despite universality of an algorithm, it is possible to note its duration of realization for groups of trainees with the average and low level of motivation. On the basis of processing of the obtained statistical data the conclusion was drawn that the efficiency of use of an algorithm for identification of motivation factors and influence on them is confirmed by growth of ability to put the obtained information into practice, manifestation of an initiative from students and pupils, the positive attitude towards the chosen specialty. Prospects of further researches of this perspective consist of psychology and pedagogical researches of vocational education motivation at different steps of professional education system.